2022
DOI: 10.3390/pharmaceutics14030490
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Decorated Cross-Linked Cytochrome c Nanoparticles for Active Targeting of Non-Small Cell Lung Carcinoma (NSCLC)

Abstract: The folate receptor alpha (FR), which is overexpressed in solid tumors including NSCLC, can be utilized for active tumor targeting to afford more effective cancer therapies. In this context, cytochrome c (Cyt c) has drawn attention to cancer research because it is non-toxic, yet, when delivered to the cytoplasm of cancer cells, can kill them by inducing apoptosis. Cyt c nanoparticles (NPs, 169 ± 9 nm) were obtained by solvent precipitation with acetonitrile, and stabilized by reversible homo-bifunctional cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Most authors reported maximal cytotoxicity, which does not exceed 60-80% using various sophisticated artificial nanoparticles bearing cytC, including solid-state dielectric as silica [63,65], hybrid gold-silica [66] and gold-ferric oxide even when cytC is combined with anticancer chemotherapeutics [67,68]. Higher cytotoxicity (up to 90%) is reached by using colloid particles prepared with cytC [69,70]. We achieved 97% cytotoxicity (ratio of dead to alive cells) in the 96th hour after addition of a suspension of the cytC-MM hybrid particles to a colon cancer cell culture [9,71] using montmorillonite colloid particles as a carrier of native cytC globules.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Most authors reported maximal cytotoxicity, which does not exceed 60-80% using various sophisticated artificial nanoparticles bearing cytC, including solid-state dielectric as silica [63,65], hybrid gold-silica [66] and gold-ferric oxide even when cytC is combined with anticancer chemotherapeutics [67,68]. Higher cytotoxicity (up to 90%) is reached by using colloid particles prepared with cytC [69,70]. We achieved 97% cytotoxicity (ratio of dead to alive cells) in the 96th hour after addition of a suspension of the cytC-MM hybrid particles to a colon cancer cell culture [9,71] using montmorillonite colloid particles as a carrier of native cytC globules.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…20 However, a major challenge associated with nanocarrier systems is achieving a high protein loading efficiency with simultaneous release of protein at the target site in its active form. 21 Many researchers have devised methods for effective cargo protein encapsulation employing various kinds of nanocarriers, including liposomes, 22 synthetic polymers, 23 natural polymers, polymeric micelles 14 and mesoporous silica nanoparticles, in order to best achieve this aim. 1,[24][25][26] It is anticipated that among these, NPs generated from naturally occurring polysaccharides will find a way towards clinical usage in the treatment of cancer due to their outstanding biocompatibility and low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%